Inisiatif GIAHS untuk Pengelolaan Lanskap Pertanian Tradisional Berkelanjutan: Studi Kasus di Desa Sudaji, Kabupaten Buleleng, Provinsi Bali - Mohammad Zaini Dahlan; Mustika Ratna Dewi; Vania Okky Putri (http://arl.faperta.ipb.ac.id/, 2020)
Traditional agricultural landscape is an important part of rural community’s life and perceived as a cultural heritage. There are various cultural values and agricultural systems with local wisdom that should be preserved. One of the strategies that can be carried out is the initiative of Globally Important Agricultural Heritage Systems (GIAHS) which promotes an agricultural landscape becomes a sustainable agricultural heritage system. However, Indonesia as an agricultural country, did not yet has any site that have been registered and participated as a GIAHS site. In fact, there is area with traditional agricultural landscape that is highly potential to be registered, namely Sudaji Village, located in Buleleng Regency, Bali. Therefore, this study aims to identify and analyze the potential and constraints of Sudaji Village regarding its agricultural landscape to be designated as GIAHS Sites in Indonesia. The methods used in this research are benchmarking method and field survey. The results showed that Sudaji Village met the five criterias to be designated as one of GIAHS Sites, as follow: (1) the contribution of the agricultural system to food security and livelihoods, (2) the use of biodiversity as a source of food and agriculture, (3) knowledge and experience of traditional community systems that are still being maintained, (4) the existence of two village government systems that affect the value system and culture of the community, and (5) the landscape condition that is influenced by people's knowledge in managing agricultural landscapes. Hopefully, Sudaji Village will become a part of the GIAHS Sites with its potentials. Keywords: benchmarking method, GIAHS Initiative, landscape management, Sudaji Village, traditional agricultural landscape